Open-pit mining complex optimization under uncertainty with integrated cut-off grade based destination policies - Paithankar, Amol; Chatterjee, Snehamoy; Goodfellow, Ryan (Resources policy, 2021)
The aim of a mining complex optimization is to maximize the economic value of the mining project as a whole. To maximize the economic value, it is required to simultaneously optimize the mining extraction sequence and destination of the material into various processing streams. This work presents a global optimization model to simultaneously optimize all aspects of the mining complex under uncertainty. To solve the mining complex problem, the method uses a combination of the maximum flow and a genetic algorithm to define the optimal production sequence, and the flow of extracted material into various destination streams are defined based on the dynamic cut-off grade optimization and block economic values. The dynamic cut-off grade is optimized using Lane's method. An application for a copper-gold mining complex indicates that the optimizer generates results that reduce the risk of not meeting the targets. When compared to commercial deterministic mine planning software, proposed algorithm generates 9.08% higher net present value and the stochastic design generated 13.70% higher expected net present value compared. Two different destination policies are evaluated to study the impact of destination policies on the net present value. Due to change in destination policies, difference of 4.36% is observed in net present value for the stochastic model. •A new solution approach for stochastic global optimization framework for open pit mining complex problems.•The method simultaneously optimizes production schedules and downstream processes.•Based on the mining production sequence estimates dynamic cut-off grades to define destination of the extracted materials.•The modeling is flexible and may be applied to numerous types of mining complexes.